Comparison Adhesive strength of Resin Composite between Total-etch and Self-etch Techniques on Enamel After Fluoride Application - Widya Saraswati; Adioro Soetojo; Yasmin Tasya Brilyanti (Conservative Dentistry Journal, 2021)
Background : White Spot Lesion (WSL) is caused by Streptococcus Mutan which causes demineralization of teeth. One of the treatments of WSL is topical application of fluoride which aims to remineralize the teeth. However, if topical fluoride treatment does not give satisfactory results, alternative treatments can be made using restorative treatments, one of which is veneers. The procedure for applying veneers requires the application of an adhesive system. The adhesive system used to apply veneers is self-etch and total-etch. Several references state that the application of fluoride which aims to remineralize teeth can influence the adhesiv strength of the restorative material using self etch and total-etch techniques. Purpose : To determine the effect of composite resin adhesion strength between total-etch and self etch techniques on enamel after fluoride application. Review : Literature sources used in the preparation of the article through several databases with descriptions of the effects of fluoride application before total-etch and/or self etch administration. From the existing references, it was found that the application of fluoride before the total-etch system had a less significant effect on the adhesiv strength. Whereas in the self etch system, fluoride application has a significant effect on the adhesiv strength. Conclusion : More references say that the application of fluoride before the total-etch system has a better adhesive strength than the application of fluoride before the self etch system